Atrial natriuretic peptide prevents cancer metastasis through vascular endothelial cells - Nojiri, Takashi (Proc Natl Acad Sci U S A, 2015)
Most patients suffering from cancer die of metastatic disease. Surgical removal of solid tumors is performed as an initial attempt to cure patients; however, surgery is often accompanied with trauma, which can promote early recurrence by provoking detachment of tumor cells into the blood stream or inducing systemic inflammation or both. We have previously reported that administration of atrial natriuretic peptide (ANP) during the perioperative period reduces inflammatory response and has a prophylactic effect on postoperative cardiopulmonary complications in lung cancer surgery. Here we demonstrate that cancer recurrence after curative surgery was significantly lower in ANP-treated patients than in control patients (surgery alone). ANP is known to bind specifically to NPR1 [also called guanylyl cyclase-A (GC-A) receptor]. In mouse models, we found that metastasis of GC-A–nonexpressing tumor cells (i.e., B16 mouse melanoma cells) to the lung was increased in vascular endothelium-specific GC-A knockout mice and decreased in vascular endothelium-specific GC-A transgenic mice compared with control mice. We examined the effect of ANP on tumor metastasis in mice treated with lipopolysaccharide, which mimics systemic inflammation induced by surgical stress. ANP inhibited the adhesion of cancer cells to pulmonary arterial and micro-vascular endothelial cells by suppressing the E-selectin expression that is promoted by inflammation. These results suggest that ANP prevents cancer metastasis by inhibiting the adhesion of tumor cells to inflamed endothelial cells.